Cultural Landscape of Sacred Forest in Baha Village, Mengwi, Badung, Bali - Karma, Made Prarabda; Paramadhyaksa, I Nyoman Widya; Witari, Made Ratna (Journal of A Sustainable Global South; Vol 8 No 2 (2024): August 2024, 2024)
The sacred forest located in the Baha Village area is a sacred place whose existence is not widely known by the general public. In fact, this forest, which was still in the territory of the Mengwi Kingdom in the past, was a forest that was highly sought after by the Aryans who came from Majapahit. Because this place is believed to give gifts to anyone related to supernatural powers. The sacredness of the forest is caused by the role of a Maharsi who comes from Puncak Mundi Temple in Nusa Penida Island. His name was Ida Ratu Sakti. However, since Japanese colonization, this sacred forest has been damaged so that the remains of the past have been destroyed or even lost. This article will explore what cultural landscapes exist in this sacred forest, and what is the relationship between Pura Dalem Alas Arum and the existing cultural landscape. The purpose of this article is to highlight the cultural landscape and the relationships between its findings, as a form of cultural preservation owned by Badung Regency and Bali Province. This research is considered qualitative research that is exploratory in nature.